Therapeutic Effect of Exosomes Derived From Stem Cells in Spinal Cord Injury: A Systematic Review Based on Animal Studies - Zhang, Cangyu; Deng, Rongrong; Zhang, Guangzhi; He, Xuegang; Chen, Haiwei; Chen, Bao; Wan, Lin; Kang, Xuewen (Frontiers in Neurology, 2022)
Objective A systematic review of the role of stem cell-derived exosomes in repairing spinal cord injury (SCI) and the existing problems in animal experiments to provide a reference for better animal experiments and clinical studies in the future. Method Three electronic databases, namely PubMed, Web of Science, and Ovid-Embase were searched. The studies were retrieved from inception to October 2021. Two researchers independently screened the literature, extracted data, and evaluated the methodological quality based on the inclusion criteria. Results and Discussion Thirty-two studies were incorporated into the final analyses. Exosomes derived from stem cells could not only significantly improve the motor function of animals with SCI, but also significantly increase the expression of anti-inflammatory factors IL-4 and IL-10 and anti-apoptotic protein Bcl-2, while significantly lowering the pro-inflammatory factor IL-1β and TNF-α and the expression of the apoptotic protein BAX. However, the mechanism of exosome-mediated SCI repair, as well as the best source and dosage remain unknown. In addition, there are still some issues with the design, implementation, and reporting of animal experiments in the included studies. Therefore, future research should further standardize the implementation and reporting of animal studies and fully explore the best strategies for exosomes to repair SCI so as to promote the translation of preclinical research results to clinical research better and faster.